Effective Strategies of Professional Communication in Academic and Business Environments - Shevchuk, Anastasia; Mokhniuk, Anna (My University, 2025)
While academic and business communication both rely on clarity, purpose, and audience focus, they differ in style. In today’s digital and global landscape, professionals need flexible, culturally aware, and tech-savvy skills. Institutions and organizations should train staff in both soft skills (e.g., listening, and adaptability) and digital tools to meet diverse communication challenges.
Keywords: academic communication; audience awareness; professional communication